EDITORIAL ARTICLE - Article Editorial (Юг России: экология, развитие, 2017)
RETRACTED ARTICLE DUE TO EXCESSIVE SELF-CITATION:Khalilov M.B., Zhuk A.F., Aytemirov A.A., Gayrabekova R.K. TAKING VARIOUS AGROTECHNICAL MEASURES FOR THE PRESERVATION AND ACCUMULATION OF MOISTURE. South of Russia: ecology, development. 2016;11(2):152-159. (In Russ.) DOI:10.18470/1992- 1098-2016-2-152-159